SPATIAL DIVERSIFICATION OF ENERGY CROPS IN POLISH AGRICULTURE: A STUDY OF PLANTATION CONCENTRATION BASED ON LOCAL INDICATORS OF SPATIAL ASSOCIATION (LISA) - Kołodziejczak, Anna; Rudnicki, Roman (Quaestiones Geographicae, 2017)
The paper deals with the spatial diversification of energy crops and their concentration in the Polish agriculture. The analysis of changes in territorial patterns regarding those plantations involves natural factors, effects of urbanisation, and the level of absorption of European Union funds. The concentration of plantations is presented by means of local spatial correlations of energy crops; for the purposes of this research, local Moran’s statistic (Ii) has also been employed.